Elaine Risley’s Character Development in Margaret Atwood’s Cat’s Eye - Nur Afifah Widyaningrum; Eddy Pursubaryanto (Lexicon, 2018)
This research explores the character development of Elaine Risley, the main character of the novel Cat’s Eye by Margaret Atwood (2009), throughout her childhood, adolescence, early adulthood, and adulthood years. The objectives of this research are to explain how the character of Elaine Risley develops in Cat’s Eye and to examine the factors which affect Elaine Risley’s character development. This research employs the objective approach proposed by Abrams (1976) as its theoretical framework and the library research as its method of research. The results show that Elaine Risley always experiences development in her character throughout her life; she develops from a bullied little girl in her childhood, a mean but passionate girl in her adolescence, and an independent young woman in her early adulthood to finally become a woman who struggles to let go of her past in her adulthood. Elaine Risley’s character development is affected by several factors, namely, Toronto as her environment, her experiences with bullying, the men and women in the society around her, her own paintings, the cat’s eye marble, and the Virgin Mary.